Estimation of Cerebral Hemodynamics and Oxygenation During Various Intensities of Rowing Exercise: An NIRS Study - Hiura, Mikio; Shirai, Yusuke; Shibutani, Hirohide; Funaki, Akio; Takahashi, Katsumi; Katayama, Yoichi (Frontiers in Physiology, 2022)
Purpose: This study aimed to investigate changes in cerebral hemodynamics and oxygenation at moderate, heavy, maximal and supramaximal intensities of rowing exercise. It also examined whether these changes reflect alterations in sensation of effort and mood. We also aimed to examine the effects of peak pulmonary oxygen consumption (V ̇O2peak) on cerebral oxygenation. Methods: Eleven rowers, consisting out of six athletes and five recreational rowers [two female; age, 27 ± 9 years; height, 171 ± 7 cm, body mass, 67 ± 9 kg; V ̇O2peak, 53.5 ± 6.5 mL min-1 kg-1] rowed a 13-minute session separated by 10 and 3 minutes, at 70% (Ex70%) and 80% of V ̇O2peak (Ex80%), respectively, on a rowing ergometer, followed by three sessions of 1-minute supramaximal exercise (ExSp). After a warm-up at 60% of V ̇O2peak (ExM), seven male rowers performed a 2000 m all-out test (Ex2000). Cardiovascular and respiratory variables were measured. Cerebral oxygenation was investigated by near-infrared time-resolved spectroscopy (TRS) to measure cerebral hemoglobin oxygen saturation (ScO2) and total hemoglobin concentration ([HbT]) in the prefrontal cortex (PFC) quantitatively. We estimated the relative changes from rest in cerebral metabolic rate for oxygen (rCMRO2) using TRS at all intensities. During Ex70% and Ex80%, ratings of perceived exertion were monitored, and alteration of the subject’s mood was evaluated using a questionnaire of Positive-and-Negative-Affect-Schedule after Ex70% and Ex80%. Results: When exercise intensity changed from Ex70% to Ex80%, the sense of effort increased while ScO2 decreased. [HbT] remained unchanged. After Ex70% and Ex80%, a negative mood state was less prominent compared to rest and was accompanied by increases in both ScO2 and [HbT]. At termination of Ex2000, ScO2 decreased by 23% compared to rest. Changes in ScO2 correlated with V ̇O2peak only during Ex2000 (r = -0.86; p= 0.01). rCMRO2 did not decrease at any intensities. Conclusion: Our results suggest that alterations in the sense of effort are associated with oxygenation in the PFC, while positive changes in mood status are associated with cerebral perfusion and oxygen metabolism estimated by TRS. At exhaustion, the cerebral metabolic rate for oxygen is maintained despite a decrease in ScO2.